Multiple effects of prefrontal lesions on task-switching - Shallice, Tim; Stuss, Donald T.; Picton, Terence W.; Alexander, Michael P.; Gillingham, Susan (Frontiers in Human Neuroscience, 2008)
This study examined the performance of 41 patients with focal prefrontal cortical lesions and 38 healthy controls on a task-switching procedure. Three different conditions were evaluated: single tasks without switches and two switching tasks with the currently relevant task signalled either 1500 ms (Long Cue) or 200 ms (Short Cue) before the stimulus. Patients with Superior Medial lesions showed both a general slowing of reaction time (RT) and a signifi cantly increased switch cost as measured by RT. No other prefrontal group showed this increased reaction time switch cost. Increased error rates in the switching conditions, on the other hand, were observed in patients with Inferior Medial lesions and, to a lesser extent, ones with Superior Medial lesions. Patients with left dorsolateral lesions (9/46v) showed slower learning of the task as indicated by a high error rate early on. Several different processes are involved in task-switching and these are selectively disrupted by lesions to specifi c areas of the frontal lobes.